Nutrition education in medical schools (NEMS) project: Joining ESPEN and university point of view. Issue 5 (May 2021) - Cuerda, C.; Muscaritoli, M.; Krznaric, Z.; Pirlich, M.; Van Gossum, A.; Schneider, S.; Ellegard, L.; Fukushima, R.; Chourdakis, M.; Della Rocca, C.; Milovanovic, D.; Lember, M.; et al.
Summary: Background & aims: Nutrition education is not well represented in the medical curriculum. The aim of this original paper was to describe the Nutrition Education in Medical Schools (NEMS) Project of the European Society for Clinical Nutrition and Metabolism (ESPEN). Methods: On 19 January 2020, a meeting was held on this topic that was attended by 51 delegates (27 council members) from 34 countries, and 13 European University representatives. Results: This article includes the contents of the meeting that concluded with the signing of the Manifesto for the Implementation of Nutrition Education in the Undergraduate Medical Curriculum. Conclusion: The meeting represented a significant step forward, moved towards implementation of nutrition education in medical education in general and in clinical practice in particular, in compliance with the aims of the ESPEN Nutrition Education Study Group (NESG).